Dashboard Utilization for Improvement in Key Performance Indicators (KPI) in Clinical Laboratory of Tertiary Care Hospital, Lahore Pakistan (Medical Forum Monthly, 2021)
Objective: To identify dashboard utilization for improvement in Key Performance Indicators in clinical laboratory of tertiary care hospital, Lahore.Study Design: Descriptive observational study.Place and Duration of Study: This study was conducted at the Pathology Laboratory of Tertiary Care setting for Four months from May to August 2020.Materials and Methods: All the samples received were entered in Laboratory Information System, identified and analyzed for reasons documented for delayed turn-around time, total critical alert reported and total no. of rejected samples calculated.Results: During 4 months of study period, 61696 samples were received, 51265 (83.09%) samples were included in the study, and 397 (0.77%) identified for documented reasons regarding key performance indicators. Out of these 397 identified samples, delayed Turnaround Time was noted in 146 (36.77), samples, total critical alerts were reported in 225 (56.6%) and 26 (6.54%) samples were analyzed as rejected. On an average, the frequency percentage of the samples analyzed was equal, but overall improvement was seen in July and August’ 2020 as compared to May and June 2020, after the introduction of dashboard laboratory information system on 1st April 2020.Conclusion: Quantitative analysis of some of the key performance indicators provided a layout of recently developed laboratory information system. The graph of KPI monitoring can be improved significantly by following standard operating procedures, using laboratory information system dashboard, coordination between the lab workers, proper training of technicians and phlebotomists. This can ensure compliance of quality lab services for patient care and safety.